2016
DOI: 10.22456/1807-9806.78248
|View full text |Cite
|
Sign up to set email alerts
|

Reconhecimento e análise das fácies sísmicas nas sucessões rift das bacias de Campos e Santos

Abstract: Apresentando reservatórios em águas profundas, o pré-sal das bacias de Campos e Santos é um cenário com depósitos heterogêneos e complexos, e assim traz novos desafios para a interpretação sísmica. O presente trabalho tem como objetivo a caracterização sísmica do intervalo rifte (de idade Hauteriviano Superior ao Barremiano, imediatamente abaixo dos reservatórios pré- -sal) nas bacias de Campos e Santos com a utilização de dados de sísmica 2D e dois perfis de poços. Foram analisadas as texturas sísmicas e com … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In a study in the adjacent Santos Basin, Barnett et al [44] showed syn-rift progradational clinoforms, with structured lateral growth, which may also indicate the original shallow water deposits in the Santos Basin. Alvarenga et al [45], based on seismic facies and attribute texture analysis, pointed to seismic facies similarities between the Campos and the Santos Basins, with the same distribution in time and space, since these seismic facies occur along the entire syn-rift section, and from shallow paleohighs to the central depocenter zones. These early studies in the Santos Basin indicate a similar situation to the Campos Basin, with some shallow zones preserving the original sediments and re-sedimented, gravity-driven deposits in deeper zones of the rifts.…”
Section: Discussionmentioning
confidence: 99%
“…In a study in the adjacent Santos Basin, Barnett et al [44] showed syn-rift progradational clinoforms, with structured lateral growth, which may also indicate the original shallow water deposits in the Santos Basin. Alvarenga et al [45], based on seismic facies and attribute texture analysis, pointed to seismic facies similarities between the Campos and the Santos Basins, with the same distribution in time and space, since these seismic facies occur along the entire syn-rift section, and from shallow paleohighs to the central depocenter zones. These early studies in the Santos Basin indicate a similar situation to the Campos Basin, with some shallow zones preserving the original sediments and re-sedimented, gravity-driven deposits in deeper zones of the rifts.…”
Section: Discussionmentioning
confidence: 99%